RESTRICTIONS ON HUMAN RIGHTS AND FREEDOMS IN QUARANTINE: HISTORICAL AND LEGAL ASPECT - Sopilko, Iryna; Maidachevska, Anastasiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Objective: to investigate some issues of quarantine restrictions on human rights and freedoms caused by coronavirus infection COVID-19, analyzing the historical aspect of the introduction of quarantine measures and current criteria for the legitimacy of restrictions on human rights and freedoms. Research methods: general philosophical, general scientific and special legal methods, in particular formal-legal, formal-logical, historical, method of analysis, method of synthesis, etc. Results: it was found that quarantine measures are effective measures to combat and deter the global threat, which states have resorted to at various stages of human history, but such measures are implemented through human rights restrictions, so they must meet international standards, be legitimate and meet the objectives rights. Discussion: human rights and freedoms are of the highest value to a democratic state, but states are forced to restrict them due to the COVID-19 pandemic; restrictions must be lawful and achieve the goal of ensuring public safety while respecting individual rights; the introduction of quarantine measures is a means of ensuring the overall security of states in the fight against disease and has a long history; any restriction of rights caused by the quarantine regime must comply with national and international law. Human rights and freedoms are of the highest value to a democracy, but they are not absolute, and the COVID-19 pandemic states are forced to restrict them by imposing quarantine measures to ensure overall security. The practice of applying quarantine restrictions on the rights of the state was resorted to decades ago, based on the effectiveness and efficiency of such restrictions in the fight against disease. However, at present, any restriction of rights caused by the quarantine regime must comply with international standards, the purpose of the law and be legitimate. Restrictions on human rights will not be arbitrary if such restrictions meet the following criteria: whether they were justified and necessary in a democratic society, and in particular whether they were proportionate and whether the reasons given by national authorities to justify them were important and sufficient.